Mockery as a special type of laugher in the prose of Leonid Andreev - Alisa V. Mytareva (RUDN Journal of Studies in Literature and Journalism)
Examines the nature of mocking laughter in the oeuvre of Leonid Andreev, defines the specifics of ridicule situations, names the participants and the possible development and resolution of the storyline. The first part of the article defines a special type of laughter - ridicule, and also examines the antithesis proposed by L.V. Karasev, “laughter - shame”. Through which the object of ridicule is characterized. The subject of research in the second part of the article is the functioning of laughter in the novels of Leonid Andreev. Using the examples of the stories Buyanikha and Laughter , it is shown that the situation of ridicule can underlie the plot and determine its development. The fear of being ridiculed is one of the significant psychological motivations that determine the behavior of L. Andreev’s heroes. In addition, the heroes endow the unknown force that influences their lives with the ability to laugh. Marking Doom, as represented by the characters, makes it more understandable, visible, and therefore surmountable. Finally, the final part examines how the picture of the “anti-world” is created, the main feature of which is ridicule. Unlike V.Ya. Propp, who argued that the object of ridicule can be everything except the area of suffering, Leonid Andreev constructs a model of the anti-world, where it is the area of suffering that is ridiculed. The ironic state of the world in relation to the hero ( Suitcases ) is perceived as unstable, and therefore unsafe. The idea of variability, the deceptiveness of the world is reflected in the depiction of necrospace in the story Peace . At the end, a conclusion is made about the connection between the themes of death and laughter in the artistic world of L. Andreev, as a distinctive feature of the writer’s work.